THE 16TH CONGRESS OF PEDIATRICIANS OF RUSSIA «ACTUAL PROBLEMS IN PEDIATRICS - A.A. Author ("Paediatrician" Publishers LLC, 2009)
(Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):128-129)